2022
DOI: 10.2105/ajph.2022.306784
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Coverage and Hesitancy Among New York City Parents of Children Aged 5–11 Years

Abstract: Objectives. To measure vaccine uptake and intentions among New York City (NYC) parents of children aged 5 to 11 years following emergency use authorization. Methods. We conducted a survey of 2506 NYC parents of children aged 5 to 11 years. We used survey weights to generate prevalence estimates of vaccine uptake and intentions. Multivariable Poisson regression models generated adjusted prevalence ratios (APRs) of vaccine hesitancy, defined as parents who reported being not very likely or not at all likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…21,60,61 The low uptake of vaccines among children and unwillingness of parents to vaccinate their children have been reported. 21,22,62,63 According to surveys in the US, 25% to 46% of parents were unsure or reluctant to vaccinate their children. 22,63,64 While 83% of parents acknowledged that "it would be bad if children got COVID-19," 63 26% did not believe that vaccines would protect their children from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,60,61 The low uptake of vaccines among children and unwillingness of parents to vaccinate their children have been reported. 21,22,62,63 According to surveys in the US, 25% to 46% of parents were unsure or reluctant to vaccinate their children. 22,63,64 While 83% of parents acknowledged that "it would be bad if children got COVID-19," 63 26% did not believe that vaccines would protect their children from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,62,63 According to surveys in the US, 25% to 46% of parents were unsure or reluctant to vaccinate their children. 22,63,64 While 83% of parents acknowledged that "it would be bad if children got COVID-19," 63 26% did not believe that vaccines would protect their children from COVID-19. Notably, even when parents themselves were vaccinated, numerous parents considered that vaccination is unnecessary for their children because they are not seriously concerned about COVID-19 risks and its complications in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in our study we found that there was no difference in influenza vaccine acceptance between groups, but families with public insurance were significantly less likely to accept the COVID-19 vaccine. Racial and socioeconomic disparities regarding COVID-19 vaccination are well documented [40,43,44] and partially rooted in issues surrounding structural racism and medical mistrust [45].…”
Section: Discussionmentioning
confidence: 99%